Assessing the Spatiotemporal Dynamic of Global Grassland Water Use Efficiency in Response to Climate Change from 2000 to 2013. (29th June 2015) - Gang, C.; Wang, Z.; Zhou, W.; Chen, Y.; Li, J.; Chen, J.; Qi, J.; Odeh, I.; Groisman, P. Y.
Abstract: Water use efficiency (WUE), which is a ratio of net primary production (NPP) to evapotranspiration (ET), is an important index representing the relationship between carbon and water cycles. This study evaluates the spatiotemporal dynamics of global grassland WUE from 2000 to 2013 to reveal the different responses of each grassland type to climate variations. Their correlations with climate variables are also investigated to reflect their dependence on climate. The average annual WUE of different grassland types follows an order of: closed shrublands > woody savannas > savannas > open shrublands > non‐woody grasslands. Although the NPP of all grassland types has increased from 2000 to 2013, 37.89 % of grassland ecosystems globally experienced a decreased WUE, in which 3.34 % has extremely significantly decreased. The WUE of open shrublands, woody savannas and non‐woody grasslands shows an overall descending trend because of the exceeding increasing rate of ET. By contrast, the decreased ET contributes to the overall ascending trend of the WUE of closed shrublands and savannas over this period. Moreover, the WUE of each grassland type reacts differently to climate variations in the northern and southern hemispheres. The grassland WUE dynamic is more controlled by precipitation than temperature at a global scale.